A systematic review on the materialistic use of Pithecellobium dulce in food formulations. (2022) - Roselin, C.; Parameshwari, Sakthivelan
Abstract: Pithecellobium dulce is a local fruit used to treat many ailments by ancient people due to its extraordinary medicinal qualities. The entire tree, from root to fruit seems to be having one medicinal quality or other. It contains bioactive compounds such as sterols, flavonoids, triterpenoids, tannins and so on and seem to have disease preventing qualities such as antiviral, antibacterial, antioxidant, anti-diabetic, anti-pyretic, anti-helminthic, anti-inflammatory, and sedative activities which are still under investigation. The fruit also contains health promoting nutrients such as proteins, plant steroids, and carbohydrates. This review revolves around the various nutritional properties and incorporation of the fruit aiding in promoting value-added novel food.